Batbat Hi Udan: A socio-cultural analysis - Albon, Decie Joy E.; Singcolan, Judith (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study aims to explore the activities, beliefs, and customs reflected in the novel Batbat Hi Udan and to understand how these aspects are still practiced and showcased by the Bukidnon tribe in contemporary times. The research seeks to answer the following questions: What activities, beliefs, and customs are depicted in the novel? How does the tribe continue to display these practices today? To achieve this, the study employed a socio-cultural analysis, which allowed for a deeper understanding of the connection between the literary work and the cultural traditions of the Bukidnon people. The study found that the activities, beliefs, and customs portrayed in Batbat Hi Udan are still alive and relevant in the current practices of the Bukidnon tribe, highlighting the tribe's strong commitment to preserving their cultural heritage. These traditions continue to be valued and passed down through generations, demonstrating literature's vital role in preserving culture. Based on these findings, the study recommends further examination of other Bukidnon literary works to enrich the knowledge of the diverse cultural practices of various tribes and to emphasize the richness of the Bukidnon tribe's cultural legacy. Through this research, it becomes evident that literature is essential in sustaining and transmitting cultural values to future generations, ensuring that the tribe's identity and customs remain intact.